2016
DOI: 10.1158/0008-5472.can-16-1131
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Artery Angiogenesis Drives Lung Tumor Growth

Abstract: Angiogenesis is vital for tumor growth but in well-vascularized organs such as the lung its importance is unclear. This situation is complicated by the fact that the lung has two separate circulations, the pulmonary and the systemic bronchial circulation. There are few relevant animal models of non-small cell lung cancer, which can be used to study the lung’s complex circulations, and mice, lacking a systemic bronchial circulation cannot be used. We report here a novel orthotopic model of non-small cell lung c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…The first comment concerns ID10, the AC lesion characterized by the lowest perfusion and shown in Figure 5 . This lesion is a very small peripheral carcinoma, one of the smallest examined, located in the subpleural parenchyma, probably characterized by a predominant pulmonary circulation, which could not have activated the angiogenesis process yet [ 37 ]. As regards the other two AC lesions with a low perfusion, ID5 in Figure 6(a) and ID15 in Figure 6(b) , these share similar properties that could explain their low perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The first comment concerns ID10, the AC lesion characterized by the lowest perfusion and shown in Figure 5 . This lesion is a very small peripheral carcinoma, one of the smallest examined, located in the subpleural parenchyma, probably characterized by a predominant pulmonary circulation, which could not have activated the angiogenesis process yet [ 37 ]. As regards the other two AC lesions with a low perfusion, ID5 in Figure 6(a) and ID15 in Figure 6(b) , these share similar properties that could explain their low perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ablation of the bronchial artery after the initiation of tumour growth resulted in significant reduction in tumour volumes at 4 weeks post‐ablation (Eldridge et al . ).…”
Section: Angiogenesis In Lung Pathologiesmentioning
confidence: 97%
“…In the few reported studies, differences exist between pulmonary and bronchial endothelial cells (Moldobaeva & Wagner, ; Eldridge et al . ), as well as aortic endothelial cells (Moldobaeva et al . ) with regard to in vitro proliferative capacity and surface marker expression.…”
Section: Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that cancer-associated fibroblasts (CAFs) in the tumor microenvironment can secrete exosomes containing lipids, amino acids, and TCA-cycle intermediates which can promote tumor growth under nutrient-stressed or nutrient-deprivation conditions [ 32 ]. Angiogenesis is also vital for tumor growth since tumor vessels are the important sources of nutrient substances in the tumor cells [ 33 ]. Tumor-derived exosomes can accelerate angiogenesis and tumor growth in a TGFβ1 (transforming growth factor β1)-dependent pathway to stimulate fibroblasts to differentiate into tumor-promoting stromal myofibroblasts [ 34 ].…”
Section: Introductionmentioning
confidence: 99%